PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERBICARA PADA SISWA KELAS V SEKOLAH DASAR: SEBUAH PENELITIAN TINDAKAN KELAS - Anis Wulansari; Adi Winanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Speaking ability is a driving factor for academic success and enhancing a more positive life. However, speaking ability still has problems such as the 5th grade students of SDN Kutowinangun 01 Salatiga. This study offers the problem-based learning model as a solution. This model has been proven at the high school until college level, so the purpose of this study was to improve speaking skills in primary school level. The research method used was action research based on Kemmis and Mc Taggart, which consists of planning, treatment and observation, and reflection. Data sources were based on direct observation and rubric assessment of speaking ability based on the components of stress, grammar, vocabulary, fluency, and comprehension. The results of descriptive statistics showed that in the pre-cycle stage only 2 students (8%) were classified as speaking skillful out of 24 students. The results of cycle 1 became 11 students (46%) and cycle 2 became 22 students (87%) who were classified as skilled speakers. The results showed that problem-based learning can improve the speaking skills of 5th grade elementary school students.